Éste no puede dirigir ninguna revolución en el Paraguay, si ni siquiera sabe hablar guaraní. - Montero, Mariano Damián (Universidad Nacional del Litoral, 2020)
The interview with Rafael Barrett, grandson of the remembered homonymous writer of the early twentieth century, brings us closer to the testimony of the only survivor to this day of the remembered expanded meeting of the Central Committee of the Paraguayan Communist Party, held in Buenos Aires, on september 11, july 1965.  There the PCP ended up breaking into two irreconcilable groups until now.  During the conversation, various negative aspects related to the internal practices of the PCP fly over, such as the cult of personality of its Secretary General, sectarianism, internal struggles, and also reflection on the armed struggle and the mistakes made